Fee Malika Sdn. Bhd. / Nur Farisha Balqis Ya’akop - Ya’akop, Nur Farisha Balqis (2020)
Fee Malika Sdn. Bhd. is one of the new comer and uprising companies in Malaysia. The company provide robust technology products. Fee Malika headquartered in Johor Bahru, Johor and was founded by Farisha Balqis. Fee Malika launched it first product Pliant Brush in 2020 along with replacement brush. The product concept is based on technology that being applied on the hair brush. Fee Malika also sell a product that match with the pliant brush that is new replacement brush. The replacement product being sell seperately and individually. Pliant brush and replacement brush will be commercial through out Malaysia, where it will be sell in all state in Malaysia. But it will focus at the market area where the population is in high density and most people around 15 to 64 yers will live there. Hence, the target market for the product pliant brush that are suitable in those age range are family household, students and backpackers. For family house hold, pliant brush is needed because it is frequently used in daily life. As for students, this pliant brush is benefical for them because they can get three items with one price. Backpackers can save some space in their luggage for other things and they do not have to brings lots things of hair care since they only need pliant brush to solve the hair problem. As for the replacement brush, the target market would be the target customer for plaint brush.